Low-energy vibrational modes in phenylene oligomers studied by THz time-domain spectroscopy - Johnston, M; Herz, L; Khan, A; Kohler, A; Davies, A; Linfield, E (2003)
Low-energy vibrational modes have been investigated in polycrystalline biphenyl, para-terphenyl, para-quaterphenyl and para-sexiphenyl using THz time-domain spectroscopy (THz-TDS). A number of both internal and external infrared-active modes were observed for wavenumbers ranging between 20 and 80 cm-1. The temperature dependence of these modes is consistent with structural phase transitions occurring in the molecular crystal, indicating that THz-TDS is a sensitive probe of the conformation of conjugated molecular systems. © 2003 Elsevier B.V. All rights reserved.